The Role of Education in the Formation of Human Sociability: Critical comparison of Th. Hobbes’ and J. J. Rousseau’s Approach - Knežić, Ivana (Journal of Education Culture and Society, 2020)
Aim: The paper aims at highlighting philosophical roots of the relation issue between nature and education in the process of socialization. Method: For the purpose of the research critical philosophical analysis and comparison of Thomas Hobbes’ and Jean-Jacques Rousseau’s texts has been used. Concept: The first part of the paper clarifies the concept of nature and explains changes in understanding of this concept thorough the history of philosophy, with the special emphasis on transformation that happened in transition from medieval to modern period. Since both Hobbes and Rousseau are representatives of modern philosophy, the second section of the paper shows how modern concept of nature manifests in the works of the two philosophers and compares, in a more detailed way, their understanding of human nature or natural state of mankind, focusing on comparison of their concepts of human natural unsociability. The third part examines more closely the role of education in transformation of human individuals into social beings. Results: Research shows that, for the two philosophers, the role of education in the process of socialization consists in denaturalization of human beings. Conclusion: Hobbes’ and Rousseau’s idea of the relation of education and nature in the process of socialization constitutes a basis for justification of manipulations of education for political ends. To avoid such manipulations and find the adequate concept of education, paper suggests to search for the adequate concept of human nature first. Key Words: education, human nature, sociability, Thomas Hobbes, Jean-Jacques Rousseau.